The role of distinct electricity sources on pollution abatement: Evidence from a wide global panel - Horobet, Alexandra; Tudor, Cristiana Doina; Belascu, Lucian; Dumitrescu, Dan Gabriel (Frontiers in Environmental Science, 2022)
In this study, we examine the contribution of nuclear, fossil (coal, oil, and gas), and renewable (hydro, solar, wind, biofuel) electricity sources to pollution in the globalization era, as measured by total greenhouse gases (GHG) produced by electricity per capita. We conduct an empirical investigation in a global panel of 163 countries which assesses both the concurrent and individual effects of alternative energy sources. Additionally, we implement a second model to assess the roles of various electricity sources on the carbon intensity of electricity generation. Robust GMM estimators show that fossil electricity is a major polluter and a driver of carbon intensity. Furthermore, nuclear and renewable energy reduce pollution on a global scale, with wind emerging as the most efficient energy source in the global fight against pollution and climate change. Moreover, globalization as measured by trade openness tends to reduce the carbon intensity of electricity production (CI), whereas biofuels have an increasing impact on CI. The findings have important policy implications, indicating that shifting to nuclear and renewable energy sources could help countries achieve their sustainable development goals more efficiently.